Pelatihan Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi EMKM pada UMKM Sepaku - Ranita Ramadhani; Rihfenti Ernayani; Hairul Anam; Dimas Rama Pramudia; Lipo Andy Willian Oey; Nadi Hernadi Moorcy (Abdimas Universal, 2022)
Currently, MSME players are increasing in number, but in their application they do not have adequate financial statements. This service was carried out in collaboration with  Balikpapan University, Micro, Small and Medium Enterprises (MSMEs) in Sepaku District. The purpose of holding community service in Sepaku District is to increase insight, expertise, and knowledge to MSME actors regarding procedures for preparing financial statements based on financial standards that can be implemented in their business operations so that MSME actors can know their financial condition and can manage and plan their finances in a more structured manner by making financial statements. The method carried out is by conducting observations, interviews with several MSMEs and providing guidebooks to MSMEs. The number of MSME participants who attended this activity amounted to 60 people. The results obtained from this activity are getting a good response, participants are expected to be able to compile and have the ability to make financial statements well.